"Read and Publish" – What It Takes to Implement a Seamless Model. Issue 1 (19th May 2021) - Anders, Andre; Chesler, Adam; Webster, Keith; Rotjan, Sara; Balduff, Drew
ABSTRACT: This article describes a program session covering the nuances and complexities of "Read and Publish" transformative agreements. The session, a panel led by Assistant Marketing Director at AIP Publishing, Sara Rotjan, included the perspectives of three individuals – the researcher, the publisher, and the librarian – to give audience members a well-rounded idea of how transformative agreements are being negotiated from various stakeholders in Open Access publishing. In addition to outlining the infrastructures of the "Read and Publish" model, panelists also detailed the unique role they play in developing and implementing "Read and Publish" models at their own institutions. They also discussed some of the challenges with "Read and Publish" models and how these challenges are being addressed by internal and external stakeholders.